2014
DOI: 10.1016/j.oraloncology.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Race and competing mortality in advanced head and neck cancer

Abstract: Black patients with advanced HNC are at increased risk of both disease progression and death from competing non-cancer mortality, particularly death from comorbid disease. Improved strategies to manage comorbid disease may increase the benefit of treatment intensification in black patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
6
29
0
Order By: Relevance
“…While net survival is useful for reporting trends in cancer survival, comparing different groups of cancer patients and investigating the impact of various factors on cancer treatment, crude probability of death is important when communicating risks to patients [10] during clinical decision making [9, 26]. Previous studies have suggested that relative survival tends to underestimate social inequalities in cancer survival; our study suggests that the Cronin-Feuer method does underestimate Indigenous to non-Indigenous disparities in cancer death probabilities (except for breast cancer) in the presence of competing risks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While net survival is useful for reporting trends in cancer survival, comparing different groups of cancer patients and investigating the impact of various factors on cancer treatment, crude probability of death is important when communicating risks to patients [10] during clinical decision making [9, 26]. Previous studies have suggested that relative survival tends to underestimate social inequalities in cancer survival; our study suggests that the Cronin-Feuer method does underestimate Indigenous to non-Indigenous disparities in cancer death probabilities (except for breast cancer) in the presence of competing risks.…”
Section: Resultsmentioning
confidence: 99%
“…Net survival is the measure most commonly used to compare cancer prognosis in different populations (e.g., between nations, regions, or racial/ethnic groups) [1, 39] because net survival removes the effect of non-cancer deaths (which may vary between populations because of different all-cause mortality rates [10]) and measures the hypothetical scenario in which patients are only able to die of their cancer. However, this is a disadvantage of net survival for patients and clinicians who, when considering the treatment options and weighing up the benefits, drawbacks, and toxicities of cancer therapy, want to know about actual prognosis: what is the chance of dying (from cancer or any cause) compared with the chance of surviving [5, 9, 10]?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in HNC outcomes research have demonstrated that African American patients face an unequal burden of disease due to differences in socioeconomic status, limited access to care, advanced cancer stage, lower receipt of treatment, and comorbidity [4][5][6][7]. Nevertheless, the existing literature focusing on racial disparities in HNC outcomes have not been able to account for relevant sociodemographic factors such as insurance, which has been suggested to have a significant impact on cancer outcomes and treatment patterns [2,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the existing literature focusing on racial disparities in HNC outcomes have not been able to account for relevant sociodemographic factors such as insurance, which has been suggested to have a significant impact on cancer outcomes and treatment patterns [2,8,9]. Additionally, the majority of existing studies do not utilize cancer specific mortality as an endpoint and are unable to account for comorbid disease that has been shown to disproportionally contribute to the mortality of African American patients with HNC [7]. Lastly, previous studies focusing on racial disparities in HNC outcomes have examined smaller cohorts restricted to few sites, thus limiting the number of pertinent covariates that could be adjusted for and generalized conclusions that could be made about disparities in HNC [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%